(untitled) (Journal of the College of Basic Education, 2022)
In this research, the researcher dealt with a very ancient word, which is (Al-Miraj), and its significance was mentioned in the previous holy books. Some have denied this miracle, so I thought that I should search for it and its roots and significance in the language through the oldest use of it. Because it contains several meanings and the word is pronounced differently according to the languages ​​of the Holy Books, the research found that (arj) has several meanings, and it is not possible to find a synonym It has its meanings, as it is ascension, elevation and inclination, and it is specific to souls, and ascension is a condition that occurs for the prophets and is not similar to the ordinary human being. With other prophets, and the research with prophets ascended to heaven, some of them mentioned the holy Quran and the Holy Book, and one of the most important recommendations of the research is to pay attention to the languages ​​of the holy books